O-299 Analyzing the impact of simple wash versus density gradient sperm preparations on intrauterine insemination outcomes. Is the cost-effective and time-efficient option just as good?. (30th June 2022) - Velmahos, C; Vagios, S; Cherouveim, P; Dimitriadis, I; Bormann, C
Abstract: Study question: How do different sperm preparations, such as simple-wash (SW) and density-gradient (DG), impact intrauterine insemination (IUI) outcomes among women seeking fertility treatments? Summary answer: Using a population from a large, academic medical center, this study discerned no differences in pregnancy outcomes between SW and DG sperm preparations. What is known already: IUI with or without ovulation induction (OI) is often a first-line treatment among couples seeking fertility services. SW and DG are two common methods used to prepare sperm for IUI. In comparison to its latter counterpart, the SW technique is lesser-used, yet is more time-efficient, and cost-effective due to its utilization of only a single centrifugation step. Since the impact of sperm preparation techniques on the post-processing sperm yield and its parameters varies by the method used, the cycle outcomes might differ as well. However, limited data exists on various sperm preparations' impact on IUI clinical outcomes. Study design, size, duration: Data from 3378 IUI+OI cycles (from 1503 women of all diagnoses seeking IUI with fresh-ejaculated sperm) that took place at a large academic fertility center between 9/2014 and 3/2021 were retrospectively reviewed. Cycles were either unstimulated (natural) or stimulated with either oral OI agents (clomiphene-citrate & letrozole) or gonadotropins. Cycles were divided in two groups based on sperm preparation technique: SW (n = 1691) and DG (n = 1687) and outcomes were compared between them. Participants/materials, setting, methods: Sperm preparation: SW semen were mixed in 10ml MHM (FujiFilm) and centrifuged for 10min. DG semen were layered over 45:90 gradient of Isolate (FujiFilm), centrifuged for 20min, and washed twice (10min) in 10ml MHM. Outcome measures: hCG-positivity (posHCGR), clinical pregnancy (CPR), spontaneous abortion (SABR), and livebirth rates/cycle (LBR). Statistics: Logistic regression with Odds Ratios (OR) adjusted for both partners' ages, day-3 FSH, stimulation, and sperm score (poor, fair, good, excellent). Sub-analysis limited cohort to first-cycles only.   Main results and the role of chance: Groups were comparable in patient [age (maternal, paternal), BMI, day-3 FSH, infertility diagnosis], and cycle characteristics [follicular response (measured as number of preovulatory follicles), and endometrial thickness]. Preprocessing sperm parameters differed slightly with higher mean sperm concentrations and lower total motility among SW cycles (75.3 + 57.0 vs. 71.0 + 51.3 million, p = 0.02; 48.6 + 19.6 vs. 52.5 + 20.2, p < 0.001, for SW and DG, respectively). posHCGR, CPR, SABR, and LBR per cycle did not differ between groups (15.8% vs. 15.4%, p = 0.76;13.7% vs. 13.2%, p = 0.62;18.1% vs. 18.5%, p = 0.93; 9.5 vs. 8.9%, p = 0.56; for SW and DG, respectively). Odds for posHCG, CP, SAB, or LB did not differ between groups [adjOR(95%CI): 1.05(0.87-1.26), p = 0.65; 1.10(0.67-1.83), p = 0.71; 0.98(0.60-1.60), p = 0.94; 1.08(0.85-1.37), p = 0.66, respectively]. When cycles were stratified by type of ovarian stimulation, rather than adjusted for it, no difference was seen in any of the clinical outcomes within individual strata{adjOR(95%CI): [Oral OI: 1.00(0.74-1.37), p = 0.98; 1.78(0.68-4.61), p = 0.25; 0.97(0.40-2.38), p = 0.95; 1.05(0.72-1.53), p = 0.81], [Gonadotropins: 0.99(0.78-1.28), p = 0.96; 0.93(0.49-1.77), p = 0.83; 0.97(0.52-1.80), p = 0.96; 1.03(0.75-1.41), p = 0.87], [Natural: 2.36(0.97-5.76), p = 0.06; 0.08(0.001-6.84), p = 0.26; 0.20(0.003-11.02), p = 0.43; 2.52(0.63-10.00), p = 0.19], for posHCG, CP, SAB, and LB, respectively}. Similarly, no difference was seen in any of the clinical outcomes when cycles were stratified by sperm score or when analysis was limited to first-cycles only. Limitations, reasons for caution: LBR were calculated excluding pregnancies with no information after discharge to obstetrics (approximately 16%). Although not significant, there might be minor variations in individual provider's practices between time frames in which these techniques were implemented. Wider implications of the findings: SW is a much simpler, time-efficient, and cost-effective sperm processing technique for IUI compared to DG, however remains infrequently utilized. Adoption of SW, over DG, could yield comparable clinical efficacy, yet optimize teamwork flow and lower healthcare costs, due to its non-labor-intensive and inexpensive nature. Trial registration number: not applicable